2012
DOI: 10.1002/jat.2788
|View full text |Cite
|
Sign up to set email alerts
|

Coffee attenuates fibrosis by decreasing the expression of TGF‐β and CTGF in a murine model of liver damage

Abstract: This study was performed to evaluate the antifibrotic properties of coffee in a model of liver damage induced by repeated administration of thioacetamide (TAA) in male Wistar rats. In this study, cirrhosis was induced by chronic TAA administration and the effects of co-administration of conventional caffeinated coffee or decaffeinated coffee (CC, DC, respectively) for 8 weeks were evaluated. TAA administration elevated serum alkaline phosphatase (AP), γ-glutamyl transpeptidase (γ-GTP) and alanine aminotransfer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
75
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(82 citation statements)
references
References 44 publications
6
75
0
1
Order By: Relevance
“…12 An array of signaling factors are involved in activating HSCs including transforming growth factor-b (TGF-b) that promotes HSC differentiation and deposition of collagen, as well as inducing hepatocyte expression of connective tissue growth factor. 12,13 Multiple studies have shown an inhibitory effect of caffeine on TGF-b, 13 as well as a decreased expression of alpha-smooth muscle actin (a-SMA), a commonly used marker for the presence of activated HSCs. 14 These suggest that the overall effect of caffeine converges on decreasing the activation of HSCs, leading to decreased deposition of collagen and fibrosis ( Table 1).…”
mentioning
confidence: 99%
“…12 An array of signaling factors are involved in activating HSCs including transforming growth factor-b (TGF-b) that promotes HSC differentiation and deposition of collagen, as well as inducing hepatocyte expression of connective tissue growth factor. 12,13 Multiple studies have shown an inhibitory effect of caffeine on TGF-b, 13 as well as a decreased expression of alpha-smooth muscle actin (a-SMA), a commonly used marker for the presence of activated HSCs. 14 These suggest that the overall effect of caffeine converges on decreasing the activation of HSCs, leading to decreased deposition of collagen and fibrosis ( Table 1).…”
mentioning
confidence: 99%
“…Coffee contains more than 1000 substances with the most important one, the chlorogenic acid (CGA) that has been found to decrease NAFLD development in rats by modulating glucose intolerance [6]. In addition, coffee has been found to reduce fibrosis in animal tissue by decreasing the expression of growth factor-b, which is responsible for the connective tissue growth factor that contributes to increase accumulation of fat in hepatic cells [7]. Furthermore, many studies have suggested the caffeine consumption plays a protective role in NAFLD [8][9][10].…”
Section: Mechanism Of Action and Dose Safetymentioning
confidence: 99%
“…Coffee consists of various compound with good 4 Based on its concentration and physiological effect, there are three main components of coffee: 5 Caffeine Caffeine (1,3,7-trimethylxanthine) is a purin alkaloid with antagonist effect on adenosine subtype A 1 and A 2A receptor. Some physiological effect of caffeine are central nervous system stimulant, raise blood pressure, increase metabolic process, and diuretic.…”
Section: Coffee and Its Componentmentioning
confidence: 99%
“…In 8-weeks therapy, coffee consumption were proved to inhibit liver tissue damage caused by TAA. 5 Caffeine could prevent hepatic and its mRNA expression. Beside that, caffeine also reduce stellate hepatic cell activation by blocking caffeine were affect MMP 2 and 9 activity.…”
mentioning
confidence: 99%